CHARACTERISTICS OF PATHOLOGIES AND NUTRITION ORGANIZATION IN LENINGRAD DURING GREAT PATRIOTIC WAR - G.L. Mikirtichan ("Paediatrician" Publishers LLC, 2010)
(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):158-162)